Relation between de body max index and the perceived motor competence in secondary education - Saioa Urrutia Gutierrez; Susana Irazusta Adarraga; Amaia Balerdi Iztueta; Oscar González Rodríguez; José Antonio Arruza Gabilondo (FEADEF, 2013)
This society, characterized by the development of knowledge, communication technologies and the generalization of transports, levels of physical activity in daily life have been declined. This has increased the sedentary lifestyle, health and nutrition related disorders and obesity. Different studies have demonstrated that this kind of co-morbidities may result from the decreased level of motor competence that has been occurring in recent years and the relation to the perception of it. At this point, we proposed to determine the relationship between body mass index and perceived motor competence. 366 subjects from 13 to 16 years have participated in this study. The weight (kg) and height (meters) of participants was measured while they were answering the AMPET-R questionnaire. The results show that there are not significant differences between different levels of body mass index and boys obtained higher values for perceived motor competence than girls. On the other hand, it has been show that body mass index and perceived motor competence are related significantly but negatively, for both girls and boys.